Alternative Organic Waste Processing Through Eco-Enzyme Manufacturing Innovation: Alternatif Pengolahan Sampah Organik Melalui Inovasi Pembuatan Eco-Enzyme - Mutiarasari, Nurul Risti; Tedjaningsih, Tenten; Suyudi, Suyudi; Suhardjadinata, Suhardjadinata (Universitas Lancang Kuning, 2024)
Agricultural development is faced with various challenges, such as climate change which can lead to food insecurity, the conversion of agricultural cultivation land to non-agriculture, population growth followed by an increase in food demand, exploitation, and degradation of agricultural land resources which causes a decrease in soil quality, environment, and agricultural products. Organic fertilizer can be obtained from the processing of organic waste which is produced either from agricultural waste or from household organic waste. Making eco-enzymes is an innovation that can be applied at the smallest level, namely households and farmer groups to be able to produce organic fertilizer. The Community Service Activity for the Food Security Scheme which was carried out in Kamulyan Village, Manonjaya District, Tasikmalaya Regency was to provide information on the concept of environmentally friendly agriculture through the manufacture of eco-enzymes as an effort to meet the demand for organic fertilizers. Next, a method is given for applying organic fertilizer from eco-enzyme fermentation to plants. This solution is offered considering the various benefits of eco-enzymes, especially in meeting the organic fertilizer needs of partner farmers, which in turn can increase the knowledge, skills, and independence of farmers.